Methods Of Teaching Young People To Communication In Pedagogical Activity (Texas Journal of Multidisciplinary Studies, 2021)
In this article, it is recommended to read Psychological, pedagogical literature in teaching young people to communicate, to observe the activity of young people in the process of communication, to determine their thinking, and in this process to use psychological games , exercises, trainings, as well as to communicate according to adult data, age, gender, profession, the peculiarity of communication of the elderly, they need it is thought that it is important to apply more words to them that raise their hearts.